Best-fit contract farming models in Benin - CGIAR Research Program on Rice (2021)
We used panel data to quantify the impact of different contract attributes on rural transformation and welfare of smallholder rice farmers in Benin. Contracts which only included an agreement on price had nearly as large of an impact as did contracts with additional attributes.